Serum galectin-3 and fibroblast growth factor-23 levels in relation with type 2 diabetes and cardiovascular risk : Galectin-3 and FGF-23 in relation to diabetes and CV risk - Klisic, Aleksandra; Gluscevic, Sanja; Karakasis, Paschalis; Kotur-Stevuljevic, Jelena; Ninic, Ana (Journal of Medical Biochemistry, 2024)
Aim: The clinical utility of galectin-3 and fibroblast growth factor 23 (FGF-23) needs to be further explored since previous studies show divergent results in relation to type 2 diabetes (T2D) and cardiovascular risk. Hence, the aim of this research was to explore galectin-3 and FGF-23 in relation to T2D, as well as to examine the potential association of these biomarkers with atherosclerotic cardiovascular disease (ASCVD) risk score in Montenegrin adults.Methods: A total of 35 T2D patients and 36 controls were consecutively enrolled. Serum galectin-3 and FGF-23 were determined by ELISA. ASCVD risk score was calculated.Results: Higher serum galectin-3 levels were shown in T2D patients (p=0.016) in comparison with control group. The increase in galectin-3 levels for 1 ng/mL showed 8.5% higher probability for T2D occurrence (OR=1.085, p=0.015). FGF-23 levels did not differ between control and T2D group. Serum galectin-3 correlated with FGF-23 (ρ=0.390, p=0.001). Both galectin-3 (ρ=0.306, p=0.010) and FGF-23 (ρ=0.332, p=0.005) correlated with ASCVD risk score in bivariate Spearman’s correlation analysis, but these correlations were not retained in binary logistic regression analysis.Conclusion: Serum galectin-3 levels, but not FGF-23 are higher in T2D patients. Serum galectin-3 correlated with FGF-23. Although both biomarkers correlated with ASCVD risk score, a further statistical analysis did not confirm their independent associations with cardiovascular risk. Studies with large sample size are needed to further explore this issue.